(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
All the countries of the world developed in equally. Somecountries are highly developed economically and some other countries are stilldeveloping and some more are under developed. Several factors are responsiblefor such variations among the nations besides political factors as mentioned inthe study. Basically it depends on the matrix of factors which have cause andeffect relationship one another.